PERANAN AUDIT OPERASIONAL DALAM MENUNJANG EFEKTIVITAS KINERJA PERUSAHAAN PADA PT JASA MARGA KUALANAMU TOL - Ayu Lestari; Risuhendi Risuhendi (UNIVERSITAS DHARMAWANGSA, 2021)
In general, many companies have stopped operating because of this unable tomaintain the existence of the company. As well as service company in Indonesiawhich is engaged in the toll road services Bel Red which has very gooddevelopment. Company within carrying out its operational activites certainly haslong-term goals as well short term. Operational audit as part of to the functionimportant influence controls help managemen to measure and evaluate theactivities carried out and reduce their occurrence waste of resources used. Theformulation of the problem in this study is whether the audit is operational affectthe effectiveness of company performance at PT Jasa Marga Kualanamu Tol. Theperpose of this study is to find out what an audit is operational influence on theeffectiveness of company performance at PT Jasa Marga Kualanamu Tol. Whereis this research is a quantitative research using simple linear regression analisis.With the results of the study shows that partially operational audits influential insupporting the effectiveness of company performance at PT Jasa MargaKualanamu Tol. The effect of Operational Audit in support effectiveness of thecompany’s financial performance at PT Jasa Marga Kualanamu Tol 90% and therest is influenced by other factors not examined by 10%.